Key stage 3 geographical enquiry - Weatherly, David; Sheehan, Nicholas; Kitchen, Rebecca (Collins, 2014)
Case studies in the book will include: samples of the breadth studies at Key Stage 3, key processes in both physical and human geography, integration of higher order thinking skills to exemplify that the world is a complex and interconnected place. Enquiry topics: 1. Living in Japan - Why isn't Yuna able to play the sport she loves? -- 2. Holes in the landscape - Why should we be concerned about sinkholes? -- 3. Is fracking all that it's cracked up to be? - Is fracking a sustainable solution to the UK's energy security challenge? -- 4. Almost Armageddon! - Why did the earth nearly die at the end of the Permian period? -- 5. Disasters and risky places - Are Haiti and the Philippines risky places to live? -- 6. Don't snatch! - How is so-called 'land grabbing' affecting Africa? -- 7. Olympic spirit - Where should the 2022 Winter Olympics be held?